2007
DOI: 10.5194/angeo-25-2195-2007
|View full text |Cite
|
Sign up to set email alerts
|

High-altitude and high-latitude O<sup>+</sup> and H<sup>+</sup> outflows: the effect of finite electromagnetic turbulence wavelength

Abstract: Abstract. The energization of ions, due to interaction with electromagnetic turbulence (i.e. wave-particle interactions), has an important influence on H + and O + ions outflows in the polar region. The effects of altitude and velocity dependent wave-particle interaction on H + and O + ions outflows in the auroral region were investigated by using Monte Carlo method. The Monte Carlo simulation included the effects of altitude and velocity dependent wave-particle interaction, gravity, polarization electrostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Effects of wave-particle interactions on Lorentzian VDFs were analyzed in Pierrard and Barghouthi (2006). More recently, Barghouthi et al (2007) analyzed also the effect of finite electromagnetic turbulence wavelength on the highaltitude and high latitude O + and H + outflows. Barghouthi et al (2008) showed that altitude and velocity dependent wave-particle interactions lead to the formation of toroids at high altitude for the ion VDFs.…”
Section: Monte Carlo Simulationsmentioning
confidence: 98%
“…Effects of wave-particle interactions on Lorentzian VDFs were analyzed in Pierrard and Barghouthi (2006). More recently, Barghouthi et al (2007) analyzed also the effect of finite electromagnetic turbulence wavelength on the highaltitude and high latitude O + and H + outflows. Barghouthi et al (2008) showed that altitude and velocity dependent wave-particle interactions lead to the formation of toroids at high altitude for the ion VDFs.…”
Section: Monte Carlo Simulationsmentioning
confidence: 98%
“…Bouhram model: based on the work of Bouhram et al [2004]. For more details about this model, see Barghouthi et al [2007]; they used this model to investigate the behavior of ion outflow at high altitudes in the auroral region.…”
Section: Theoretical Formulationsmentioning
confidence: 99%
“…(1) Barghouthi and Atout [2006] investigated the effects of altitude and velocity dependent wave‐particle interaction on H + and O + outflows at high altitude and high latitude by using Monte Carlo simulation; they reported that the effect of finite gyroradius is responsible for production of the H + and O + toroids at high altitudes equatorward of the cusp that are observed by TIDE and TIMAS ion instruments on board the polar spacecraft. (2) Barghouthi et al [2007] investigated H + and O + outflows at high altitude and high latitude by using a combined (altitude part from Barghouthi [1997] and velocity part from Bouhram et al [2004]) form for the diffusion coefficient. They found that including the effect of finite electromagnetic turbulence wavelength, i.e., the effect of velocity‐dependent diffusion coefficient and consequently, the velocity‐dependent wave‐particle interaction, produces realistic H + and O + temperatures and H + and O + toroids, and this is qualitatively consistent with the observations of H + and O + ions in the auroral region at high altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that such results may interpret as finite perpendicular wavelength effects in the WPI. The velocity dependence of the diffusion coefficient due to Bouhram et al (2004) is investigated in Barghouthi et al (2007). This paper shows that Bouhram diffusion coefficient produces H + and O + conics at low altitudes and toroids at higher altitudes, with an elongated tail in the upward direction because mirror force dominates the perpendicular heating due to WPI.…”
Section: Introductionmentioning
confidence: 95%